ALGAL DIVERSITY IN TEA AND PINEAPPLE PLANTATION SOILS IN MARNGAR, MEGHALAYA (INDIA) (Applied Biological Research, 2025)
The algal distribution in farmland depends on the plantation type and soil properties, therefore the present study was aimed to assess the diversity of algal community in soils of tea- and pineapple-plantation soils and to correlate the relationship between algae and soil parameters. Soil samples were collected from tea- and pineapple-plantations every month from April 2022 to May 2023. The soil and algal samples were analyzed by appropriate standard methods. Tea plantation soil was clay loam while pineapple plantation soil was sandy loam. The soil samples from study sites were slightly acidic throughout the season. Significant differences in both the study sites were observed for conductivity, moisture content, water holding capacity, organic carbon and phosphorus content. Some frequently encountered algal species were Calothrix marchica, Oscillatoria limnetica, Phormidium retzii, Chlamydomonas reinhardii, Scenedesmus communis, Scenedesmus dimorphus, Gomphonema parvulum, and Navicula lanceolata. A total of 63 algal species were recorded from both the sites. Maximum species diversity was observed in tea plantation soil with diversity index of 2.56. Higher algal abundance was noted in the root zone of tea plantation. The soil physicochemical parameters and plantation type significantly influenced the occurrence, composition and abundance of algae in tea- and pineapple-plantation soils.
Keywords: Algal diversity; physicochemical properties; pineapple plantation; soil; tea plantation